The Impact of Personal Thoracic Impedance on Electrical Cardioversion in Patients with Atrial Arrhythmias - Seung-Young Roh; Jinhee Ahn; Kwang-No Lee; Yong-Soo Baek; Dong-Hyeok Kim; Dae-In Lee; Jaemin Shim; Jong-Il Choi; Young-Hoon Kim (Medicina, 2021)
Background and Objectives: Direct current cardioversion (DCCV) is a safe and useful treatment for atrial tachyarrhythmias. In the past, the energy delivered in DCCV was decided upon empirically, based only on the type of tachyarrhythmia. This conventional method does not consider individual factors and may lead to unnecessary electrical damage. Materials and Methods: We performed DCCV in patients with atrial tachyarrhythmias. The impedance and electrical current at the moment of shock were measured. The human thoracic impedance between both defibrillator patches and the electric current that was used were measured. Results: A total of 683 DCCVs were performed on 466 atrial tachyarrhythmia patients. The average impedance was 64 ± 11 Ω and the average successful current was 23 ± 6 mA. The magnitude of the electrical current that was successful depended upon the human impedance (linear regression, B = −0.266, p < 0.001) and the left atrial diameter (B = 0.092, p < 0.001). Impedance was directly proportional to body mass index (BMI) (B = 1.598, p < 0.001) and was higher in females than in males (77 ± 15 Ω vs. 63 ± 11 Ω, p < 0.001). Notably, the high-impedance (>70 Ω) group had a higher BMI (27 ± 4 kg/m2 vs. 25 ± 3 kg/m2, p < 0.001) and a higher proportion of females (37% vs. 9%, p < 0.001) than the low-impedance group (<70 Ω). However, thoracic impedance was not an independent predictor for successful DCCV. Conclusions: Human thoracic impedance was one of the factors that impacted the level of electrical current required for successful DCCV in patients with atrial arrhythmias. In the future, it will be helpful to consider individual predictors, such as BMI and gender, to minimize electrical damage during DCCV.